A tenure-clock problem - Chia-Hui Chen; Junichiro Ishida (Osaka University, Institute of Social and Economic Research (ISER), 2015)
We consider a "tenure-clock problem" in which a principal may set a deadline by which she needs to evaluate an agent's ability and decides whether to promote him or not. We embed this problem in a continuous-time model with both hidden action and hidden information, where the principal must induce the agent to exert effort to facilitate her learning process. The value of committing to a deadline is examined in this environment, and factors that make the deadline more profitable are identified. Our simple framework allows us to obtain a complete characterization of the equilibrium, both with and without commitment, and provides insight into why up-or-out contracts are prevalent in some industries while they are almost non-existent in others.
Keywords: D82; D83; 330; dynamic agency; deadlines; experimentation; standard promotion practices; up-or-out contracts